Association of time of first corticosteroid treatment with bronchopulmonary dysplasia in preterm infants. Issue 10 (11th August 2021) - Cuna, Alain; Lagatta, Joanne M.; Savani, Rashmin C.; Vyas‐Read, Shilpa; Engle, William A.; Rose, Rebecca S.; DiGeronimo, Robert; Logan, J. Wells; Mikhael, Michel; Natarajan, Girija; Truog, William E.; Kielt, Matthew; et al.
Abstract: Objective: To evaluate the association between the time of first systemic corticosteroid initiation and bronchopulmonary dysplasia (BPD) in preterm infants. Study design: A multi‐center retrospective cohort study from January 2010 to December 2016 using the Children's Hospitals Neonatal Database and Pediatric Health Information System database was conducted. The study population included preterm infants <32 weeks' gestation treated with systemic corticosteroids after 7 days of age and before 34 weeks' postmenstrual age. Stepwise multivariable logistic regression was used to assess the association between timing of corticosteroid initiation and the development of Grade 2 or 3 BPD as defined by the 2019 Neonatal Research Network criteria. Results: We identified 598 corticosteroid‐treated infants (median gestational age 25 weeks, median birth weight 760 g). Of these, 47% (280 of 598) were first treated at 8–21 days, 25% (148 of 598) were first treated at 22–35 days, 14% (86 of 598) were first treated at 36–49 days, and 14% (84 of 598) were first treated at >50 days. Infants first treated at 36‐49 days (aOR 2.0, 95% CI 1.1–3.7) and >50 days (aOR 1.9, 95% CI 1.04–3.3) had higher independent odds of developing Grade 2 or 3 BPD when compared to infants treated at 8–21 days after adjusting for birth characteristics, admission characteristics, center, and co‐morbidities. Conclusions: Among preterm infants treated with systemic corticosteroids in routine clinical practice, later initiation of treatment was associated with a higher likelihood to develop Grade 2 or 3 BPD when compared to earlier treatment.